Burger's Medicinal Chemistry and Drug Discovery 2003
DOI: 10.1002/0471266949.bmc011
|View full text |Cite
|
Sign up to set email alerts
|

NMRand Drug Discovery

Abstract: In this chapter we give an overview of the two major approaches used in NMR and drug discovery: structure‐based design and NMR‐based screening. Combined with the more traditional uses of NMR in medicinal chemistry, they demonstrate the versatility of NMR as a tool for drug discovery. Structure‐based design is considered in two parts, ligand‐based design and receptor‐based design. In the former, NMR provides information on structure elucidation of drug leads, conformational analysis, charge state, tautomeric eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 184 publications
0
2
0
Order By: Relevance
“…Their unique circular backbone topology and knotted arrangement of three disulfide bonds makes them exceptionally stable to thermal and enzymatic degradation (Scheme 1).Furthermore, their well-defined structures have been associated with a wide range of biological functions. [2,3] Cyclotides MCoTI-I/II are powerful trypsin inhibitors (K i % 20-30 pm) that have been recently isolated from the dormant seeds of Momordica cochinchinensis, a plant member of the cucurbitaceae family. [4] Although MCoTI cyclotides do not share significant sequence homology with other cyclotides beyond the presence of the three cystine bridges, structural analysis by NMR spectroscopy has shown that they adopt a similar backbone-cyclic cystine-knot topology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their unique circular backbone topology and knotted arrangement of three disulfide bonds makes them exceptionally stable to thermal and enzymatic degradation (Scheme 1).Furthermore, their well-defined structures have been associated with a wide range of biological functions. [2,3] Cyclotides MCoTI-I/II are powerful trypsin inhibitors (K i % 20-30 pm) that have been recently isolated from the dormant seeds of Momordica cochinchinensis, a plant member of the cucurbitaceae family. [4] Although MCoTI cyclotides do not share significant sequence homology with other cyclotides beyond the presence of the three cystine bridges, structural analysis by NMR spectroscopy has shown that they adopt a similar backbone-cyclic cystine-knot topology.…”
mentioning
confidence: 99%
“…S 2 values for residues 5 and 23 from free MCoTI-I are not included in the average because the relaxation data could not be fitted to a monoexponential function. [b] S 2 values for residues2,5,8,18,19,23,29,31,32, and 33 from trypsin-bound MCoTI-I are not included in the…”
mentioning
confidence: 99%